Sistem Informasi Pencarian Jasa Tukang Berbasis Web (Analysis) - Zikrillah, Arif; Gusman, Deddy (PT Pustaka Cendekia Group, 2023)
At this time there are still many people who have difficulty finding someone to help with work that cannot be done based on their own abilities, such as in the case of building houses, building, repairing houses/buildings and so on. If such a problem occurs, of course it will be a problem in overcoming these things. To overcome this, special expertise and skills are needed in carrying out the work, namely workers who have services in development. A handyman certainly has various kinds of skills, such as building houses, repairing leaky roofs, painting houses, installing electrical installations, making fences, and so on. A craftsman's skills can be owned by more than one craftsman, meanwhile the users of the handyman's services also have various needs. to overcome the problems that exist in the community in finding builders according to the services needed and this search process can be carried out through the website so that it can save time and according to the desired needs.